Persistence of Infarct Zone T2 Hyperintensity at 6 Months After Acute ST-Segment–Elevation Myocardial Infarction: Incidence, Pathophysiology, and Prognostic Implications. (December 2017) - Carberry, Jaclyn; Carrick, David; Haig, Caroline; Ahmed, Nadeem; Mordi, Ify; McEntegart, Margaret; Petrie, Mark C.; Eteiba, Hany; Hood, Stuart; Watkins, Stuart; Lindsay, Mitchell; Davie, Andrew; et al.
Abstract : Background—: The incidence and clinical significance of persistent T2 hyperintensity after acute ST-segment–elevation myocardial infarction (STEMI) is uncertain. Methods and Results—: Patients who sustained an acute STEMI were enrolled in a cohort study (BHF MR-MI: NCT02072850). Two hundred eighty-three STEMI patients (mean age, 59±12 years; 75% male) had cardiac magnetic resonance with T2 mapping performed at 2 days and 6 months post-STEMI. Persisting T2 hyperintensity was defined as infarct T2 >2 SDs from remote T2 at 6 months. Infarct zone T2 was higher than remote zone T2 at 2 days (66.3±6.1 versus 49.7±2.1 ms; P <0.001) and 6 months (56.8±4.5 versus 49.7±2.3 ms; P <0.001). Remote zone T2 did not change over time (mean change, 0.0±2.7 ms; P =0.837), whereas infarct zone T2 decreased (−9.5±6.4 ms; P <0.001). At 6 months, T2 hyperintensity persisted in 189 (67%) patients, who were more likely to have Thrombus in Myocardial Infarction flow 0 or 1 in the culprit artery ( P =0.020), incomplete ST-segment resolution ( P =0.037), and higher troponin ( P =0.024). Persistent T2 hyperintensity was associated with NT-proBNP (N-terminal pro-B-type natriuretic peptide) concentration (0.57 on a log scale [0.42–0.72]; P =0.004) and the likelihood of adverse left ventricular remodeling (>20% change in left ventricular end-diastolic volume; 21.91 [2.75–174.29]; P =0.004). Persistent T2 hyperintensity was associated with all-cause death and heart failure, but the result was not significant ( P =0.051). ΔT2 was associated with all-cause death and heart failure ( P =0.004) and major adverse cardiac events ( P =0.013). Conclusions—: Persistent T2 hyperintensity occurs in two thirds of STEMI patients. Persistent T2 hyperintensity was associated with the initial STEMI severity, adverse remodeling, and long-term health outcome. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02072850. Abstract : Supplemental Digital Content is available in the text.